Determinants of COVID-19 Vaccine Hesitancy: A Cross-Sectional Study on a Mexican Population Using an Online Questionnaire (COV-AHQ) - Juan Luis Delgado-Gallegos (Frontiers Media S.A., 2021)
Mexico has become one of the most highly affected countries by coronavirus disease 2019 (COVID-19) pandemic in Latin America. Therefore, efficient vaccination programs are needed to address COVID-19 pandemic. Although recent advances around the world have made it possible to develop vaccines in record time, there has been increasing fear and misinformation around the vaccines. Hence, understanding vaccine hesitancy is imperative for modeling successful vaccination strategies. In this study, we analyzed the attitude and perceptions toward COVID-19 vaccination, in a Mexican population (n = 1,512), using the proposed COVID-19 Vaccine Acceptance and Hesitancy Questionnaire (COV-AHQ) (Cronbach's alpha > 0.8), which evaluates a mild perception of danger and contamination with respect to COVID-19, a moderate perception of xenophobia generated throughout COVID-19 quarantine, fear of adverse effects of COVID-19 vaccination, and hesitancy of parent toward vaccination of children; furthermore, a section including sociodemographic variables was included. According to the results of this study, the statistical correlation analysis of the general vaccination posture seems to correlate significantly (p < 0.05) with a mild perception of danger and contamination with respect to COVID-19, a moderate perception of xenophobia generated throughout COVID-19 quarantine, hesitancy of parent toward vaccination of children, willingness to get COVID-19 vaccine, previous influenza vaccination, perception of the vaccine that could help the economy of country, occupation, gender, age, and participants actively researching COVID-19 vaccine information. An in-depth analysis assisted by binary logistic regression concluded that the young adult population around ages 18–34 years are the most likely to get vaccinated. This posture seems to be highly influenced by a mild perception of danger and contamination with respect to COVID-19, a moderate perception of xenophobia generated throughout COVID-19 quarantine, fear of adverse effects of COVID-19 vaccination, and hesitancy of parents toward vaccination of children. While their own personal religious beliefs and economic status, the level of education does not seem to have an effect on the willingness to get vaccinated neither did having a previous COVID-19 diagnosis or even knowing someone with a positive COVID-19 diagnosis. Health authorities and policymakers could use the results of this study to aid in modeling vaccination programs and strategies and identify population groups with high vaccine hesitancy prevalence and assess significant public health issues.